Estudo energético dos geradores fotovoltaicos do IFAM-CMDI - Assis, Carlos Magno Cássio de (Brasil, 2024)
Brazil is one of the countries with the greatest potential for absorbing energy from the sun due to its location being close to the equator. Previous studies already carried out apply to only estimating this potential using data on irradiation levels, while few studies have con-ducted statistical modeling with software that incorporates various types of photovoltaic mo-dules of current inverters and their efficiency,system losses and data on local weather condi-tions. The Software (SAM) calculates the performance of photovoltaic systems based on local climatic conditions and data entered into its database of all components with their respective model and manufacturer to carry out the computational calculation. It is, therefore, a very effective tool for determining the viability of a photovoltaic project before its implementation and afterwards for energy estimation. The main objective of this work is to use SAM to esti-mate the energy production throughout the year of the 9 photovoltaic generators installed on the roof of IFAM-CMDI and consequently point out if there is any incompatibility between the simulated generation and the one generated on site that was extracted by the remote mo-nitoring software for GOODWE inverters.